Rituximab for the treatment of eosinophilic granulomatosis with polyangiitis (Churg–Strauss). Issue 2 (2nd December 2014) - Mohammad, A J; Hot, A; Arndt, F; Moosig, F; Guerry, M-J; Amudala, N; Smith, R; Sivasothy, P; Guillevin, L; Merkel, P A; Jayne, D R W
Abstract : Background: Conventional treatment of eosinophilic granulomatosis with polyangiitis (EGPA) (Churg–Strauss) with glucocorticoids, with or without additional immunosuppressive drugs, is limited by partial efficacy, frequent toxicity and a high relapse rate. Rituximab is a licensed treatment for granulomatosis with polyangiitis and microscopic polyangiitis and is of potential benefit to patients with EGPA. Methods: Patients with EGPA who received rituximab as single or repeated courses were identified from four vasculitis centres. Standardised data collection was performed, including disease activity status and adverse events, at the time of initial treatment and after 6 and 12 months. Remission was defined as a Birmingham Vasculitis Activity Score (BVAS) of 0 and partial response as a ≥50% reduction in BVAS compared with baseline. Results: 41 patients (21 women) with EGPA treated with rituximab between 2003 and 2013 were identified. 15 (37%) had refractory, 21 (51%) relapsing and 5 (12%) new onset disease. 19 received a single course and 22 received repeat-dose rituximab to prevent relapse. By 6 months, 83% improved with remission in 34% and partial response in 49%, and by 12 months 49% were in remission and 39% had a partial response. Prednisolone doses decreased in all patients by 6 and 12 months. Antineutrophil cytoplasmic antibody positivity at baseline was associated with a higher remission rate at 12 months. Adverse events included 15 infections (6 were severe). Conclusions: The treatment of EGPA with rituximab resulted in high rates of improvement and reduced requirement of prednisolone. Rituximab may be considered for the treatment of EGPA.